2022
DOI: 10.3389/ijph.2022.1604217
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Excessive Recreational Screen Time Among Colombian Children and Adolescents

Abstract: Objectives: Excessive recreational screen time (RST) is associated with detrimental effects for physical, psychological and cognitive development. This article aims to describe the prevalence of excessive RST among Colombian preschoolers, children and adolescents and explore its factors associated.Methods: We analyzed data from the National Survey of Nutrition 2015. The sample included 4,503 preschoolers, 5,333 school-aged children and 6,623 adolescents. Poisson regression models with robust variance were cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…This supports the observation that adolescents tend to consume unhealthy food and drinks during their screen time [ 24 ]. This has already been reported in other multicultural countries: young people consume unhealthy food in front of screens in Brazil [ 43 ] and Colombia [ 44 ], where this link between unhealthy food consumption and screen time is greater in urban areas. Indeed, media advertising may encourage adolescents to consume more unhealthy food and drinks [ 25 , 29 , 45 ].…”
Section: Discussionsupporting
confidence: 65%
“…This supports the observation that adolescents tend to consume unhealthy food and drinks during their screen time [ 24 ]. This has already been reported in other multicultural countries: young people consume unhealthy food in front of screens in Brazil [ 43 ] and Colombia [ 44 ], where this link between unhealthy food consumption and screen time is greater in urban areas. Indeed, media advertising may encourage adolescents to consume more unhealthy food and drinks [ 25 , 29 , 45 ].…”
Section: Discussionsupporting
confidence: 65%
“…Considering similar research on the subject; negative educational situations are also observed in studies of overrecreation among Colombian preschoolers, children and adolescents (González et al, 2022). Also a study conducted in the western United States states that the risk of forest fires has increased as a result of excessive recreation in the region where outdoor recreation is most intense.…”
Section: Discussionmentioning
confidence: 77%
“…In addition to a different outcome variable, the difference in the findings between their study and our study might involve the cross-sectional design employed in their study, thus ignoring the potential lagged effects. In fact, strong evidence has proven the importance of parents as being both “gatekeepers” and “role models” in shaping children’s screen use behaviors [ 26 , 28 ]. Parents’ nonscreen-related behaviors may not impact children’s ST as directly as parents’ screen-related parenting practices, such as rule setting (gatekeepers) or parental screen use (role models), but they are expressions of the household’s shared value toward healthy living [ 16 ].…”
Section: Discussionmentioning
confidence: 99%